Real heat : gender and race in the urban fire service - Chetkovich, Carol A. (Rutgers University Press, 1997)
"In the struggle over affirmative action, no employment setting has seen more friction than urban fire departments. Thirty years of legal and political efforts have opened the doors of this historically white male preserve, but men of color have yet to consolidate their gains, and women's progress has been even more tenuous. In this unique and compelling account of affirmative action at the "street level," Carol Chetkovich explores the ways in which this program has succeeded and failed." "Chetkovich follows the men and women of the Oakland Fire Department Class 1-91 through their academy training and eighteen-month probation. Real Heat explores how the process of becoming a firefighter interacts with the dimensions of race and gender to support some and discourage others."--Jacket